The University Museum as a Place of Visibility, Credibility, Versatility and Viability of Culture - Molina León, María (Eikón / Imago, 2019)
The existence of the University Museums is linked to the so-called third mission of the University: the dissemination of Culture as a tool for social transformation. They exist at the service of the intra university community and ad extra at the service of the general public. They must be part of Strategic Plans of Culture and Heritage within the University, of the structures and budgets enabled, of the accurate diagnosis and of the general objectives that are marked at the corporate level. Only in this way will they be places of visibility, credibility, versatility and viability of culture in 21th century and not just a pretext or an expendable ornament in the Universities.